SIFAT MATERIAL POLYESTER HYBRID COMPOSITE - BATANG BEMBAN (Donax Canniformis) - Akhmad Syarief; Akhmad Yafie (Scientific Journal of Mechanical Engineering Kinematika, 2017)
Bemban (Donax Canniformis) is a plant similar to rattan, the stem produces fiber woven material. This plant has other names bamban, bumban, bomban, and so forth. Composites are a new type of material combined with two or more ingredients and have different properties with each other both physical properties and chemical properties. From the research of this hybrid composite stem rod, it is known in the specimens of impact test of volume fraction 60% bemban (Energy Absorption 21,11 J and Impact Price 0,0332 J / mm²) has the most optimum ductility than volume fraction 40% Energy Absorption 20.62 J and Impact Price 0.0324 J / mm²) and 50% bemban bemban (Energy Absorption 20,96 J and Impact Price 0.0330 J / mm²). In bending test specimens, the volume fraction of 60% bemban stem (Bending Strength 0.45 MPa) has the most optimum ductility properties compared to the volume fraction of 40% bemban rod (Bending Strength 0.63 MPa) and 50% bemban (Bending Strength 0.72 MPa). In tensile specimens fraction volume of 60% bemban rod (Tensile Strength 0.00449 MPa) has the most optimum ductility properties compared to volume fraction of 40% bemban rod (Tensile Strength 0.00224 MPa) and 50% bemban rod (Pull Strength 0.00284 MPa).